Efforts to Improve Discipline Through Storytelling Methods Using Hand Puppets at PAUD Bahrul Ihsan Ciamis - Nurjanah; Intan Fauziyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The basis of this research aims to: First, to understand how learning planning uses the storytelling method with hand puppet media to improve children's discipline. Second, to understand how to implement the storytelling method using hand puppets in order to improve early childhood discipline. Third, to understand whether there is an increase in the development of children's discipline through the storytelling method using hand puppets. The research method used is Classroom Action Research (PTK) Kemmis Mc. Taggart. Data collection techniques using the method of observation, interviews, and documentation. The data analysis technique used is qualitative data analysis (data reduction, data description, and conclusions) and uses averages to find out the results of actions that can lead to improvements, improvements, and changes in research. The results of the research are: First, learning planning through the storytelling method using hand puppet media which begins with determining the learning theme, making a Daily Learning Implementation Plan (RPPH), preparing learning media, carrying out activities, and carrying out assessments. Second, the implementation of learning is carried out in II cycles, each cycle consisting of 3 meetings with the theme of Nature Aemesta, Sub-Theme of Natural Objects, sub-theme of water, stone and fire, in accordance with the RPPH with opening, core and closing activities. . The three storytelling methods using hand puppet media have an impact on the development of student discipline in each cycle with an average cycle I meeting I 1.80 showing the Undeveloped category (BB), meeting II 2.00 showing the Starting to Develop category (MB), meeting III 2.31 shows the Start Developing category (MB). Followed by the second cycle, meeting I 2.71 showed the category of Starting to Develop (MB), meeting II 2.97 with the category Starting to Develop (MB), meeting III with a value of 3.14 in the category Developing According to Expectations (BSH).